Prospective study comparing enzyme‐linked immunosorbent assay and glycoarray assay to detect antiglycolipid antibodies in a routine diagnostic neuroimmunology laboratory setting. Issue 2 (14th January 2015) - Delmont, Emilien; Robb, Henry; Davidson, Amy; Halstead, Susan; Yao, Denggao; Meehan, Gavin R.; Willison, Hugh
Abstract Objective Enzyme‐linked immunosorbent assay (ELISA) is the conventional technique for antiglycolipid antibody testing in inflammatory neuropathy sera. Miniaturized array‐based assays (glycoarrays) have also been used to detect these antibodies. As previous studies have focused on specific disease categories, such as Guillain–Barré syndrome, the array has never been tested on an unselected population in a routine diagnostic laboratory setting. Methods In the present prospective study, we compared the results of the glycoarray with data obtained with a standardized inflammatory neuropathy cause and treatment‐ELISA. A total of 300 sera sent to the Glasgow Neuroimmunology Laboratory for routine antiglycolipid antibody testing during a 6‐month period were tested both with ELISA and glycoarray. Results The two techniques were significantly correlated and showed good agreement. By ELISA, six sera were positive for immunoglobulin G antibodies against GM1 or GD1a, 11 for immunoglobulin G anti‐GQ1b antibodies, five for immunoglobulin M anti‐GM1 antibodies and three for immunoglobulin M antibodies against disialosyl gangliosides. The glycoarray had a sensitivity of 92% to detect ELISA‐positive sera with a specificity above 92% for all the different ELISA patterns. Conclusions The glycoarray allows testing of large panels of antibodies against single glycolipids and complexes of glycolipids on a very small scale. Its technical characteristics make it suitable as a diagnostic screening test. As data provided by the glycoarray and ELISA were reliably correlated in the present study, the glycoarray can be used in a routine setting to detect antiglycolipid antibodies. Further studies, including more positive samples, are required to clarify the future position of the array in the biological investigation of inflammatory neuropathies.